STRATEGI PENGEMBANGAN ENERGI TERBARUKAN CINA DALAM RENCANA LIMA TAHUN KE-13 UNTUK MEMENUHI CAPAIAN SDG7 - Rama Capriano Arnesto Putra; Iwan Ridwan Zaelani (Paradigma POLISTAAT: Jurnal Ilmu Sosial dan Ilmu Politik, 2021)
This article aims to identify China's renewable energy development strategy in the 13th Five-Year Plan to meet SDG7 achievements. The development of renewable energy is an important part of sustainable development. Renewable energy is implicitly regulated in the 7th goal of the Sustainable Development Goals (SDG7) which was agreed in September 2015. China as one of the countries carrying out the energy transition process has a major role in ensuring the achievement of SDG7. To ensure the development of renewable energy, China has formulated a renewable energy development agenda in one of its policies, namely, the 13th Five Year Plan for the 2016-2020 period. Using descriptive research methods and SWOT analysis methods, this study examines the types of strategies used by the Chinese Government in ensuring the development of renewable energy to meet the achievements set out in SDG7. This article finds that the Chinese Government established four types of strategies in the 13th Five-Year Plan. This strategy is the main concept of China's renewable energy development in ensuring the achievement of SDG7 in the 2016-2020 period.